Fathers in Work Organizations Inequalities and Capabilities, Rationalities and Politics - Liebig, Brigitte; Oechsle, Mechtild (Verlag Barbara Budrich, 2017)
This book is dedicated to the role of work organizations when it comes to the realization of an active fatherhood. Firstly, it deals with barriers for active fatherhood and its correlating mechanisms of inequality: Which aspects of discrimination and social closure do fathers face today if they assert a claim for active fatherhood, and with what kind of barriers are they confronted? Secondly, capabilities of fathers are addressed: Which is their possible scope of action, and which factors lead to differences in capabilities at the workplace? Finally, the book analyzes the meaning of organizational rationalities, and the effects of policies and programs on change and organizational learning with respect to fatherhood.